(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This scientific article examines the role of monetary policy in ensuring economic stability and growth. Through extensive review and analysis, the work explores the impact of monetary policy on key macroeconomic variables, including inflation, production, and employment. The article reveals the decisive role of monetary policy in stabilizing the economy by holding inflation and managing the business cycle.